2019
DOI: 10.26434/chemrxiv.11328242.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comonomer Strategy for Triggered Degradation and Re/Upcycling of High-Performance Thermoset Plastics

Abstract: Thermosets play a key role in the modern plastics and rubber industries, comprising ~18% of polymeric materials with a worldwide annual production of 65 million tons. The high density of crosslinks that give these materials their useful properties comes at the expense of facile degradability and re/upcyclability. Here, using the high-performance industrial thermoset plastic poly-dicyclopentadiene (pDCPD) as a model system, we show that when a small number of cleavable bonds are selectively installed within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
(59 reference statements)
0
14
0
1
Order By: Relevance
“…Degradation of CyMeSi-based thermosets also occurred at 10% v/v, consistent with our previous findings using analogous 8-membered ring silyl ether comonomers (Figures 2B and S11−S13). 19 At higher loadings, the dissolution of NbMeSi-doped thermosets slowed, with 20, 33, 50, and 100% v/v samples mostly or partially dissolving at TBAF exposure times as long as 1 week. By contrast, CyMeSibased materials dissolved quickly at all loadings greater than 5% v/v.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Degradation of CyMeSi-based thermosets also occurred at 10% v/v, consistent with our previous findings using analogous 8-membered ring silyl ether comonomers (Figures 2B and S11−S13). 19 At higher loadings, the dissolution of NbMeSi-doped thermosets slowed, with 20, 33, 50, and 100% v/v samples mostly or partially dissolving at TBAF exposure times as long as 1 week. By contrast, CyMeSibased materials dissolved quickly at all loadings greater than 5% v/v.…”
mentioning
confidence: 95%
“…Recently, we demonstrated that incorporation of ∼10% v/v of cleavable silyl-ether-based comonomer additives into pDCPD enables its chemical deconstruction into reusable oligomeric fragments without impacting many properties of virgin pDCPD such as Young's modulus, % strain at break, toughness, thermal stability, and ballistic impact response (Figure 1B). 19 Nevertheless, the introduction of conforma-tionally flexible comonomers resulted in significant, dosedependent decreases in T g as estimated through the peak of the tan(δ) curve from dynamic mechanical analysis (DMA) (up to 28 °C at 10% v/v). Others have reported similar T g depression when pDCPD is formed in the presence of comonomers rather than crosslinkers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The development of new reaction methodologies and advanced (macro)molecular architectures and topologies will further fuel the design of polymer networks with fascinating behaviors and improved mechanical properties. In addition, practical, scalable synthetic strategies are necessary to meet the existential need for sustainable polymer networks, next‐generation energy storage/harvesting materials, separations membranes, and catalysts. Finally, new tools for the generation of polymer network databases amenable to advanced computational screening and machine learning are highly sought after .…”
Section: Discussionmentioning
confidence: 99%
“…Die Entwicklung neuer Reaktionsmethoden und hochentwickelter (makro)molekularer Architekturen und Topologien wird die Erschließung von Polymernetzwerken mit faszinierendem Verhalten und verbesserten mechanischen Eigenschaften weiter vorantreiben. Außerdem sind geeignete, skalierbare Synthesemethoden erforderlich, um den existenziellen Bedarf an nachhaltigen Polymernetzwerken, Materialien für die Energiespeicherung bzw. Energieernte, Trennmembranen und Katalysatoren zu decken.…”
Section: Zusammenfassung Und Ausblickunclassified